Comparison of coronary revascularization strategies in older adults presenting with acute coronary syndromes. Issue 8 (16th April 2022) - Shah, Ahmed Ijaz; Alabaster, Amy; Dontsi, Makdine; Rana, Jamal S.; Solomon, Matthew D.; Krishnaswami, Ashok
Abstract: Background: The optimal coronary revascularization strategy to maximize the patient‐centered outcome of days alive and out of hospital (DAOH), in multimorbid older (≥65‐years) adults after an acute coronary syndrome (ACS) is incompletely understood. Methods: Using Kaiser Permanente Northern California Health Plan databases, we identified 3871 patients ≥65‐years presenting with ACS between 1/1/2010–3/1/2018 who underwent coronary revascularization with either coronary artery bypass grafting (CABG, N  = 1575) or multivessel percutaneous coronary intervention (PCI, N  = 2296). Selection bias was accounted for through propensity score modeling techniques and inverse probability of treatment weighting. Cox proportional hazards models were fit to evaluate the association of revascularization type with outcomes. Primary Outcomes: Absolute DAOH and the relative risk of achieving ≥90%DAOH during three time intervals. Secondary Outcomes: All‐cause mortality, recurrent MI, stroke, rehospitalization, repeat revascularization, and dialysis initiation. Results: CABG (compared to PCI) was associated with greater absolute number of DAOH, significant after the first year (mean difference at 1‐year: +5.8 days, 95% confidence interval [CI], −1.6 to 13 days; 3‐years: +56 days, 95%CI, +25 to +88 days; 5‐years: + 131 days, 95%CI, +57 to +205 days). The relative risk of achieving ≥90% DAOH significantly favored CABG after the first year (1‐year:1.02, 95%CI, 0.98–1.05; 3‐years:1.06, 95%CI 1.002–1.11, 5‐years:1.12, 95%CI, 1.03–1.22), and was related to lower incidences of all‐cause mortality, repeat revascularization, rehospitalization, incident dialysis, and nonfatal MI with CABG. Conclusions: In older adults with multivessel or left main coronary artery disease who presented with ACS, CABG, after the first year, was associated with a greater absolute number of DAOH—a geriatric and patient‐centered outcome, compared to PCI. CABG patients also had a higher probability of achieving ≥90%DAOH—with lower all‐cause mortality, recurrent MI, repeat revascularization, new dialysis, and rehospitalization rates. Future randomized trials should study the impact of optimal revascularization strategies on the quality of life of older adults with multimorbidity. Abstract : See related editorial by Hanna et al . in this issue.